More frequent IgD and reduced CD200 expression in Chinese patients younger than 50 years old with multiple myeloma: a multicenter analysis - Lu J; Lu J; Chen W; Wang J; Huo Y; Hou J; Huang X (Dove Medical Press, 2016)
Jin Lu,1,* Jing Lu,2,* Wenming Chen,3,* Jing Wang,1 Yuliang Huo,4 Jian Hou,2 Xiaojun Huang1 1Department of Hematology, People’s Hospital, Beijing University, Beijing, People’s Republic of China; 2Department of Hematology, The Myeloma and Lymphoma Center, Changzheng Hospital, The Second Military Medical University, Shanghai, People’s Republic of China; 3Department of Hematology, Beijing Chaoyang Hospital, Capital Medical University, Beijing, People’s Republic of China; 4Data Management Department, Beijing University Clinical Research Institute, Beijing, People’s Republic of China *These authors contributed equally to this work Abstract: We retrospectively analyzed the presenting features and survival of 194 newly diagnosed patients with multiple myeloma in the People’s Republic of China. Compared with older patients, younger patients had a higher percentage of IgD isotype, lower percentage of International Staging System Stage 3 disease, higher albumin level, and lower frequency of high ß2-microglobulin and CD200 expression. There was no difference in sex, Durie–Salmon stage, bone lesion degree, creatinine, lactate dehydrogenase, fluorescence in situ hybridization, and expression of other antigens. Among all 940 newly diagnosed patients with multiple myeloma, those younger than 50 years had better overall survival and progression-free survival than older patients. Of these patients, 457 were treated with a bortezomib-containing regimen, and 450 received conventional therapy. Younger patients treated with bortezomib had better overall survival and progression-free survival than older patients. However, younger patients treated with conventional therapy had the same survival as older patients. Keywords: multiple myeloma, age, survival, China